IMPLEMENTASI PERATURAN DAERAH NOMOR 12 TAHUN 2013 TENTANG PENGELOLAAN, PEMBERDAYAAN DAN PERLINDUNGAN PASAR TRADISIONAL KOTA SALATIGA - Adi, Elwin Himawan; ., Susilo Utomo; ., Yuwanto . (Journal of Politic and Government Studies, 2017)
The Implementation of Regional Regulation Number 12 of 2013 on the Management, Empowerment, and Protection of Traditional Market in SalatigaABSTRACTThe aim of this research was to investigate the implementation of Regional Regulation number 12 of 2013 on the management, empowerment, and protection of Traditional Market that took place on Blauran Traditional Market in Salatiga. Municipal Administration of Salatiga does the implementation of Regional Regulation to maintain the existence of Traditional Market on the rapid development of Modern Stores. This study analyzed how the implementer does the management, empowerment, and protection of Traditional Market on Blauran Traditional Market that became the highlight in this study. The researcher chose Blauran Traditional Market in Salatiga as a case study research. The method used in this study was a qualitative research method with in-depth interview method and observation. In obtaining the data, the researcher interviewed the research informants which are Department of Industry, Trade, and Cooperatives and Micro, Small, Medium Enterprises of Salatiga and also Regional Technical Implementation Unit district II. It was analyzed used George Edward III theory. In addition, the researcher used secondary data derived from documentation data in Department of Industry, Trade, and Cooperatives and Micro, Small, Medium Enterprises of Salatiga.The finding of this study shows that the implementation of Regional Regulation concerning Management, Empowerment and Protection of Traditional Markets in Salatiga has not been run in accordance with the regulations that have been made, with the initial goal is to maintain the existence of Traditional Markets Salatiga of rapid Modern Shop. This is evidenced by the failure of the government through the Department of Salatiga and UPTD market to meet the needs of target groups in implementing aspects of management, empowerment and protection of traditional markets. Of the 15 Traditional Market in the city of Salatiga not all traditional market that has implemented the three aspects of Regulation Number 12 of 2013, namely Management, Empowerment and Protection of Traditional Market. Government Salatiga through the Department less active role in the implementation of this law on managing the existence of market vendors, provide guidance to the merchant market and provide physical facilities through the renovation of traditional markets and support facilities Traditional Markets in Salatiga, but in the aspect of protection of traditional market in the provision of location strategic and profitable been fulfilled by the Government of Salatiga to provide locations in strategic places.Keywords: Regional Regulation, Traditional Market